High-resolution mapping of global winter-triticeae crops using a sample-free identification method - Y. Fu; X. Chen; C. Song; X. Huang; J. Dong; Q. Peng; W. Yuan (Earth System Science Data)
Winter-triticeae crops, such as winter wheat, winter barley, winter rye and triticale, are important in human diets and are planted worldwide, and thus accurate spatial distribution information on winter-triticeae crops is crucial for monitoring crop production and food security. However, there is still a lack of global high-resolution maps of winter-triticeae crops because of the reliance of existing crop mapping methods on training samples, which limits their application at the global scale. In this study, we propose a new method based on the Winter-Triticeae Crops Index (WTCI) for global winter-triticeae crop mapping. This is a new sample-free method for identifying winter-triticeae crops based on differences in their normalized difference vegetation index (NDVI) characteristics from the heading to harvesting stages and those of other types of vegetation. We considered state (or province) or country to be an identification unit and employed the WTCI to produce the first global 30 m resolution distribution maps of winter-triticeae crops from 2017 to 2022 using Landsat and Sentinel images. Validation using field survey samples and visual interpretation samples from Google Earth images indicated that the method exhibited satisfying performance and stable spatiotemporal transferability, with producer's accuracy, user's accuracy and overall accuracy values of 81.12 %, 87.85 % and 87.7 %, respectively. Moreover, compared with the Cropland Data Layer (CDL) and EuroCrops datasets, the overall accuracy and F1 score in most regions of the United States and Europe were more than 80 % and 75 %, respectively. The identified area of winter-triticeae crops was consistent with the agricultural statistical area in almost all the investigated countries or regions, and the correlation coefficient (R2) between the identified area and the statistical area was over 0.6, while the relative mean absolute error (RMAE) was less than 30 % in all 6 years. Overall, this study provides a reliable and automatic identification method for winter-triticeae crops without any training samples. The high-resolution distribution maps of global winter-triticeae crops are expected to support multiple agricultural applications. The distribution maps can be obtained at https://doi.org/10.57760/sciencedb.12361 (Fu et al., 2023a).